Research Innovation to Support the Commersialization of Biopesticides in Indonesia - Supriadi, Supriadi (Puslitbang Perkebunan, 2015)
ABSTRACTThe economic value of biological pesticides outside Indonesia is quite high, reaching US 1.8 billion, however, in Indonesia, the value is insignificant. The paper was aimed to discuss the commercialization of biological pesticides and research innovation to support its development. The biological pesticide formulation in Indonesia is limited; only 30 formulas (0.6%) are registered of the total 2475 registered pesticide formulations in 2012. The Ministry of Agriculture has produced 39 biological pesticide formulations that could be developed by pesticide companies for commercialization. The limited number of the registered biological pesticides shows serious constraints on their commercialization. One of the important constraint is lacking of standardization of the active ingredients and the formulations are short life. The Government, through The Ministry of Agriculture, emposes the Permentan no.39/ Permentan/SR.330/7/2015 in effort to encourage the commercialization of biological pesticides. The registrartion of biological pesticide do not require acute oral and dermal toxict data as that applied to synthetic pesticides. In addition, any government agency that has the duty and function of plant protection can apply for registration of biological pesticide. To improve the quality of biological pesticides that will attract investors, the role of research programs related to improving the quality of the biological pesticide formulation is needed.Keywords: Biological pesticides, innovation, research innovation 16 Volume 14 Nomor 1, Juni 2015 : 15 -25Â Inovasi Hasil Penelitian untuk Mendukung Komersialisasi Pestisida Biologi di IndonesiaABSTRAKNilai ekonomi pestisida biologi di luar negeri cukup tinggi, yaitu mencapai US 1,8 milyar, tetapi di Indonesia nilainya belum memadai. Makalah ini membahas kendala komersialisasi pestsida biologi dan dukungan inovasi penelitian untuk pengem-bangannya. Jumlah formulasi pestisida biologi di Indonesia masih terbatas; hanya 30 (0,6%) dari total 2475 formulasi pestisida yang terdaftar pada tahun 2012. Kementerian Pertanian telah menghasilkan 39 inovasi formulasi pestisida biologi yang siap dikembangkan oleh perusahaan pestisida untuk komersialisasi. Terbatasnya formula pestisida biologi yang diperdagangkan menunjukkan adanya kendala dalam komersialisasinya. Kendala utamanya adalah belum adanya standardisasi mutu bahan aktif dan masa simpan bahan aktif sangat pendek (short life). Upaya Pemerintah untuk mendorong komersialisasi pestisida biologi ditunjukkan dengan terbitnya Permentan No.39/Permentan/SR.330/7/2015. Dalam Permentan tersebut, pendaftaran pestisida biologi tidak mensyaratkan data hasil uji toksisitas akut oral dan akut dermal sebagaimana diberlakukan untuk pestisida sintetis. Di samping itu, instansi Pemerintah yang mempunyai tugas dan fungsi perlindungan tanaman dapat mengusulkan pendaftaran untuk pestisida biologi. Untuk meningkatkan mutu pestisida biologi yang masih beragam perlu dibuat standar bakunya sehingga keefektifannya bisa terjamin sehingga akan menarik investor untuk mengembangkannya. Oleh karena itu, peran penelitian berkaitan dengan peningkatan mutu formulasi pestisida biologi sangat diperlukan.Kata kunci: Pestisida biologi, inovasi, dukungan penelitian